Critical temperature ranges of hypothermia-induced platelet activation: Possible implications for cooling patients in cardiac surgery - Straub, Andreas; Breuer, Melanie; Wendel, Hans P.; Peter, Karlheinz; Dietz, Klaus; Ziemer, Gerhard (Thrombosis and Haemostasis, 2007)
Cooling of the patient is routinely applied in cardiac surgery to protect organs against ischemia. Hypothermia induces activation of platelets, but the effects of temperatures such as used during cardiac surgery are not well described. To investigate this in an in-vitro study heparinized whole blood was incubated at different temperatures (37°C, 34.5°C, 32°C, 29.5°C, 27°C, 24.5°C, 22°C, 19.5°C and 17°C).The effect of these temperatures on aggregation, P-selectin expression, GP IIb/IIIa activation and platelet microparticle (PMP) formation of unstimulated and ADP-stimulated platelets of 36 subjects was evaluated in flow cytometry. A four-parametric logistic model was fitted to depict the temperature effect on platelet parameters. Lower temperatures increased aggregates, P-selectin expression, and GP IIb/IIIa activation. The number of PMPs decreases with hypothermia. Additional experiments revealed a slight influence of heparin on platelet P-selectin expression but excluded an effect of this anticoagulant on the other evaluated parameters. Threshold temperatures, which mark 5% changes of platelet parameters compared to values at 37°C, were calculated. On ADP-stimulated platelets the thresholds for P-selectin expression and GP IIb/IIIa activation are 34.0°C and 36.4°C, respectively, and lie in the temperature range routinely applied in cardiac surgery. Hypothermia- induced platelet activation may develop in most patients undergoing cardiac surgery, possibly resulting in thromboembolic events, coagulation defects, and proinflammatory leukocyte bridging by P-selectin bearing platelets and PMPs. These findings suggest that pharmacological protection of platelets against hypothermia-induced damage may be beneficial during cardiac surgery.
Keywords: Platelet physiology; cell-cell interactions; surgery; platelet glycoproteins